THE DEVELOPMENT OF THE LEARNING CD BASED ON FLASH MULTIMEDIA TO INCREASE THE MEMORIZING SHORT CHAPTERS STUDENTS COMPETENCE IN MI AL-KHADIJAH MALANG - Uyun, Fitratul (Proceeding of International Conference on Islamic Education (ICIED); Vol 3 No 1 (2018): Proceeding of International Conference on Islamic Education (ICIED), 2018)
Learning media is used as an attractive means so that the material presented is easier to understand or understand by students. The development of multimedia learning media can overcome the gap between ideal conditions and real conditions. in this study, researchers used this type of development research. research and development methods or better known as research and development (R & D) by using the learning development design of Walter Dick and Lou Carey.  The results obtained after implementing learning CD media is learning has a high level of efficiency and high attractiveness and can be said learning CD media have good quality.